The modified multilayer coverage of urethroplasty for distal hypospadias - Mohamed Oulad Saiad (Wolters Kluwer Medknow Publications, 2018)
Purpose: Our purpose is to present the modified multilayer coverage to prevent fistula and to present also the glans dissection respecting the continuity between glans and corpus spongiosum. We think an important factor for glans vascularization that prevents glans disruption for patients with distal hypospadias and report the follow-up. Introduction: Fistula and glans disruption are still the most frequent complications of hypospadias surgery. Neourethral coverage is a mandatory step in this challenging surgery; it reduces the rate of fistula. Materials and Methods: Between September 2013 and December 2015, the modified multilayer coverage using two or three intermediate layers was performed in 110 patients with distal and midshaft hypospadias. Follow-up based on local examination, visual assessment of urine stream, and parent satisfaction was recorded at 1, 3, 6 months, 1 year, and yearly thereafter. Patients lost for the follow-up and the circumcised patients with a bad quality remaining dorsal dartos are excluded from the study. Results: Intraoperatively, the decision whether two or three intermediate layers should be performed depending on the type of the hypospadias and the presence of hypoplastic urethra. Among the 88 patients retained for the study, 86 patients presented satisfactory results, but one patient had a fistula that healed spontaneously and the second patient had a glans disruption. Conclusions: The modified multilayer coverage with a wings glans dissection respecting the continuity of spongiosum and glans is a reliable procedure to reduce the rate of fistula and glans disruption in anterior and midshaft hypospadias.